Produção de Na-β″-alumina e o seu transporte iônico do Na+ - Pitoli, Andrew Correia Lacerda (2019)
In the present doctorate thesis, in order to study the Na+ ion transport in Na-βʺ-alumina(cr), we started by studying the production stages of Na-βʺ-alumina(cr) sodium ion conductive membranes. In order to do so, we studied the stages of (i) synthesis of Na-βʺ-alumina(cr) powder from physical mixtures of powder Na2CO3(cr) and Al2O3(cr, α) precursors, (ii) forming of green-bodies (i. e., geometrically compacted particle arrays) and, at last, (iii) sintering of circular flat plates membranes. In the synthesis stage, we identified the phase Na2O∙Al2O3(cr) as an stable intermediate, and obtained Na-βʺ-alumina(cr) at temperatures as low as 1000 °C in a traditional tubular horizontal Joule Effect heated furnace built by us. In the forming stage, we were able to reproducibly obtain green-bodies in a cylindrically hollow metal die (projected exclusively for this purpose) without usage of binding nor lubricant agents. In the sintering stage, we were able to produce sintered membranes with noticeably higher mechanical resistance and (in some of them) lower apparent volume of the heat treated green-bodies. During sintering, we registered mass losses for every produced membrane, probably due to undesired incongruent sublimation of Na2O from Na-βʺ-alumina(cr). The extent of mass losses would be higher for higher temperatures and higher isothermal periods employed in the sintering stage. These losses could be attenuated by the usage of support-powder, with the same composition as the green-bodies, burying the green-bodies. The depth of mass losses would’ve been enough to shift the system’s global composition to lesser Na2O contents in the Na-βʺ-alumina(cr) variable composition region. We were able to determine the temperature region in which the sintering kinetic control would shift from mechanisms that would cause sintering without apparent volume shrinkage to mechanisms that would cause sintering with shrinkage, at about 1550 °C (Na-βʺ-alumina(cr) upper thermal stability limit). For the sintering stage, we also developed and adapted a household microwave oven into a furnace able to conduct controlled time-variable temperature heating schedules up to 1520 °C. Interpretations about the possible kinetic processes studied are presented, alongside their respective probable chemical equations. At last, we were able to conduct preliminary electrochemical measurements (galvanostatic, open circuit potential measurements, and electrochemical impedance spectroscopy) on a two-compartment cell in which our membranes (acting as separators) were immersed in Na+ ion conductive molten salts. These results indicated that Na+ ion transport through the membranes was achieved, yet we weren’t able to control the system in study.